Plant N Fluxes and Modulation by Nitrogen, Heat and Water Stresses: A Review Based on Comparison of Legumes and Non Legume Plants - Christophe, Salon; Jean-Christophe, Avice; Annabelle, Larmure; Alain, Ourry; Marion, Prudent; Anne-Sophie, Voisin (IntechOpen, 2011)
None